GEANT 4 simulation of the Helios cosmic ray telescope E6: Feasibility of chemical composition studies. (July 2015) - Marquardt, J; Heber, B; Hörlöck, M; Kühl, P; Wimmer-Schweingruber, R F
Abstract: In October 2011, ESA announced the selection of Solar Orbiter as one of the Cosmic Vision M missions. It's launch is foreseen in 2018. Therefore it is worthwhile to revisit the energetic particle measurements together with the solar wind and magnetic field data from Helios in light of better theoretical understanding and advanced analysis and modelling techniques developed during the past 20 years. In this contribution we will present a GEANT 4 simulation of the response function of the Helios E6 experiment, that measured electrons in the energy range from a few 100 keV to above 10 MeV, ions from 1 MeV/nucleon to above 50 MeV/nucleon, and its application to the data analysis with respect to the chemical composition of the Galactic Cosmic Rays.